The impact of environmental taxes on transportation and storage enterprises’ development – the case of Balkan countries - Sadowski, Adam; Misztal, Anna; Kowalska, Magdalena; Jędrzejczak, Ryszard; Engelseth, Per; Bujak, Andrzej; Skowron-Grabowska, Beata (Technological and Economic Development of Economy, 2023)
Sustainable development counteracts climate change and strives for a good quality of life. It is a development based on economic, social and environmental goals which should be evaluated. Environmental taxes have to ensure enterprises’ development follows sustainability principles. The basis of environmental taxes is a physical unit of harmful substance emissions with a proven negative impact on the environment. The article’s main objective is to assess the impact of environmental taxes (Envtax) on the sustainable development of the transportation and storage enterprises (Susd) (NACE Rev. 2: H) from 2008 to 2018. We created integrated indicators of sustainable development and its components, single-equation and multi-equation models (the OLS estimation) and Model Autoregressive Moving Average with eXogenous (ARMAX) to verify the research hypothesis. The research results indicate that energy (Entax t), transport (Trtax) and pollution taxes (Poltax) from current and previous period significantly affect the development of transportation and storage enterprises within sustainability principles (economic: Ed, social: Sd, and environmental: Envd). There is a strong variation in the strength and direction of the impact of environmental taxes on the development of the transportation and storage enterprises following sustainability principles in Bulgaria, Croatia, Romania, and Slovenia from 2008 to 2018. The results indicate that taxes are not effectively used and that implementing reforms in the European Union in this area is the right direction.